2013
DOI: 10.1177/0954405413511073
|View full text |Cite
|
Sign up to set email alerts
|

Statistical multi-objective optimization of electrical discharge machining parameters in machining titanium grade 5 alloy using graphite electrode

Abstract: In industrial applications, particularly in aero, marine and medical industries, titanium has received great attention as a useful material and electrical discharge machining as its machining process. Selection of optimal machining parameters in a multi-objective environment is essential for specific workpiece and tool material combination, which is the concern of industries to improve the overall productivity at less cost. In this article, optimization of critical electrical discharge machining parameters suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Sivam et al 42 performed multi-objective optimization of EDM parameters for machining of holes in titanium grade 5 alloy using graphite electrodes. They reported that as per the analysis of variance (ANOVA) table, the most effective parameters are the pulse on-time, pulse current and pulse off-time.…”
Section: Research Trends On Micro-edm Of Difficult-to-machine Materiamentioning
confidence: 99%
“…Sivam et al 42 performed multi-objective optimization of EDM parameters for machining of holes in titanium grade 5 alloy using graphite electrodes. They reported that as per the analysis of variance (ANOVA) table, the most effective parameters are the pulse on-time, pulse current and pulse off-time.…”
Section: Research Trends On Micro-edm Of Difficult-to-machine Materiamentioning
confidence: 99%
“…Generally, the following methods are used in EDM to remove debris deposits: Z-axis retraction, flushing, EDM parameter optimization, and electrode planetary motion. 714 However, large-scale machining and hemisphere machining involve area effect as well as materials with special geometric shapes that hinder machining debris removal. Therefore, this study combined slotted electrodes with rotary machining to improve the debris removal effect, increase MRRs, obtain the optimal slotted electrode model, and analyze the electrical discharge waveforms.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical discharge machining (EDM) is carried out by a series of repetitive discharge pulses produced between the tool electrode and the workpiece. 1 Owing to its unique noncontact machining characteristics, EDM has become one of the most popular micro machining techniques. More and more attention has been paid to micro EDM, especially in the industries of aerospace, die and mold making, automotive, medical and so on.…”
Section: Introductionmentioning
confidence: 99%